Therapeutic effects of yoga and mindfulness on cancer-related pain: a literature-based review - Savchak, Tetiana; Ivanchuk, Sofiia; Kaminskaya, Anhelina; Kurek, Aleksandra; Feretycki, Hubert; Głowacka, Aleksandra; Górecki, Patryk; Kozicki, Maciej; Salama, Aladdin; Domińczak, Dominika; et al. (Quality in Sport, 2026)
Purpose of research: This literature-based review was created to evaluate the effectiveness of yoga and mindfulness-based interventions (MBIs) in managing chronic and acute cancer-related pain. Research materials and methods: A systematic review of literature from 2012 - 2026 across databases including PubMed, Scopus, and Web of Science was conducted. Full-text versions of Meta-Analyses, Systematic Reviews, and Randomized Controlled Trials were included. Basic results: The analysis demonstrates significant reductions in pain interference (how much pain interferes in daily life) and improvements in pain threshold across different groups of patients. Mind-body practices effectively down-regulate pro-inflammatory markers and salivary cortisol. Efficacy was validated in pediatric care, peripheral neuropathy, and through various cognitive-behavioral approaches. Conclusions: Yoga and mindfulness serve as cost-effective, low-risk non-pharmacological aid that improves the quality of life (QoL) in oncology patients. Keywords: Oncology, Mindfulness-Based Stress Reduction (MBSR), Hatha Yoga, Chronic Pain, Palliative Care.